Accounting for syntax in analyses of countersinging reveals hidden vocal dynamics in a songbird with a large repertoire. (September 2017) - Hedley, Richard W.; Denton, Kaleda K.; Weiss, Robert E.
Abstract : Identifying the signalling strategies employed by animals during vocal interactions is a challenge, especially for species with large vocal repertoires. We propose that efforts to study such vocal dynamics can benefit by integrating models of syntax into their analyses. In this study, we conducted playback experiments on Cassin's vireo, Vireo cassinii, to examine the role of syntax, and more specifically, shared syntactic patterns, in countersinging. We presented 11 males with song sequences ordered according to population norms, and with sequences whose order deviated from population norms. We did not find evidence that individuals markedly altered their responses based on the syntax of the playback, either in their physical approach to the speaker or in the quantity of song they delivered in response. We did, however, find evidence that syntax was important in governing their choice of phrase types in response to the playbacks. Subjects did not match the playback phrase types. Instead, they engaged in a vocal behaviour referred to as song advancing, where they responded to a stimulus phrase type by singing the phrase type that most often followed the stimulus in their own normal song sequences. When playback sequences were ordered according to population norms, song advancing resulted in birds pre-empting the upcoming playback phrase type or delivering another of the prior playback phrase types (i.e. delayed matching) at higher rates than when playback sequences deviated from population norms. The detection of song advancing was only possible with the explicit inclusion of syntax in our analysis, suggesting that studies of the vocal interactions of species with repertoires of multiple vocalizations can benefit from consideration not only of a subject's repertoire, but also their syntax. Highlights: We incorporated models of syntax into analysis of vocal responses to playback. Birds responded to a phrase by singing the next phrase in their preferred sequence. Factors were analysed that affected the probability of song advancing. Taking syntax into account is a powerful method for studying vocal interactions.